1998
DOI: 10.1128/mcb.18.7.3727
|View full text |Cite
|
Sign up to set email alerts
|

SBA1 Encodes a Yeast Hsp90 Cochaperone That Is Homologous to Vertebrate p23 Proteins

Abstract: The Saccharomyces cerevisiae SBA1 gene was cloned by PCR amplification from yeast genomic DNA following its identification as encoding an ortholog of human p23, an Hsp90 cochaperone. The SBA1 gene product is constitutively expressed and nonessential, although a disruption mutant grew more slowly than the wild type at both 18 and 37°C. A double deletion of SBA1 and STI1, encoding an Hsp90 cochaperone, displayed synthetic growth defects. Affinity isolation of histidine-tagged Sba1p (Sba1 His6 ) after expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
146
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 61 publications
(85 reference statements)
7
146
0
2
Order By: Relevance
“…He showed that deletion of the p23 gene of Saccharomyces cerevisiae had a minimal effect on GR action, but it did sensitize the GR to inhibition by the GA-related drug, macbecin II (42). Another report by Fang et al (43) showed that the deletion of yeast p23 resulted in only a mild reduction in cell growth or the hsp90-dependent activities of the tyrosine kinase v-Src and the androgen receptor. Our results show a marked dependence upon p23 for the generation of hormone binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…He showed that deletion of the p23 gene of Saccharomyces cerevisiae had a minimal effect on GR action, but it did sensitize the GR to inhibition by the GA-related drug, macbecin II (42). Another report by Fang et al (43) showed that the deletion of yeast p23 resulted in only a mild reduction in cell growth or the hsp90-dependent activities of the tyrosine kinase v-Src and the androgen receptor. Our results show a marked dependence upon p23 for the generation of hormone binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, comparison of the results presented here with those previously reported using heterologous clients reveals some common trends. Deletion of CPR6 or SBA1, for example, results in a only a slight defect in v-Src or nuclear receptor signaling, whereas deletion of CPR7 or YDJ1 resulted in strong signaling defects (Kimura et al, 1995;Dey et al, 1996;Duina et al, 1996;Warth et al, 1997;Fang et al, 1998). By correlation, cochaperones that are essential for viability are also likely to play essential roles in the folding pathway; examples here are Cdc37 and Cns1.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the cochaperones are required for this reaction is not clear, because purified Hsp70 and Hsp90 can together facilitate folding of GR in vitro, whereas cochaperones such as Hop stimulate the reaction (Morishima et al, 2000;Rajapandi et al, 2000). Furthermore, deletion of yeast Hop (STI1), or p23 (SBA1) does not result in a slow growth phenotype except under stress conditions (Nicolet and Craig, 1989;Chang et al, 1997;Bohen, 1998;Fang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations